Italian women writers, 1800-2000 : boundaries, borders, and transgression - Sambuco, Patrizia, 1965- (Fairleigh Dickinson University Press ; The Rowman & Littlefield Publishing Group, Inc., 2015)
This book investigates narrative, autobiography, and poetry by Italian women writers from the nineteenth century to today and considers the topics of boundaries and borders in their writings.